Does women directorship in Malaysian government-linked companies matters? - Soong Yu Qing, Hooy Chee-Wooi (Universiti Pendidikan Sultan Idris, 2016)
Does women directorship in Malaysian government-linked companies matters? by Soong Yu Qing, Hooy Chee-Wooi,